Enhanced Piperine Solubility and Dissolution Rate in Piperine-Nicotinamide Multicomponent Crystal Adsorbed in Mesoporous Silica SBA-15 - Fitriani, Lili; Fauziah, Gusrina; Hasanah, Uswatul; Agustin, Rini; Zaini, Erizal (Science and Technology Indonesia, 2026)
Piperine, classified as a Class II substance in the Biopharmaceutics Classification System (BCS), has poor solubility in water but high permeability. This research aims to improve the solubility and dissolution rate of piperine by adsorbing a multicomponent crystal (MCC) of piperine-nicotinamide onto mesoporous silica SBA-15. Tetraethyl orthosilicate (TEOS) was used as a silica precursor and Pluronic P123 as a pore-formation template to create SBA-15. Adsorption of the MCC was carried out by solvent evaporation with MCC:SBA-15 mass ratio (1:1). Solid state characterization was carried out by nitrogen adsorption-desorption isotherm, X-ray powder diffraction (XRPD), differential scanning calorimetry (DSC), Fourier-transform infrared (FT-IR) spectroscopy, and scanning electron microscopy (SEM). Solubility tests were carried out for 24 hours and the dissolution rate profile was conducted for 60 minutes in distilled water. Dissolved piperine was determined using high performance liquid chromatography (HPLC) with methanol and distilled water as the mobile phase (75:25). The physical stability of MCC:SBA-15 was evaluated at various high relative humidities. The solid-state characterization results showed successful adsorption of the MCC in SBA-15 with a decrease in surface area, pore volume, and intensity of the X-ray diffraction peaks. The FT-IR spectrum of MCC:SBA-15 resembled that of SBA-15. The solubility test results showed 2.47-fold and 3.07-fold increases in solubility and dissolution rate compared to pure piperine, respectively. MCC:SBA-15 demonstrated high stability at 75% and 85% RH at 40◦C. In conclusion, adsorption of the MCC piperine-nicotinamide crystal in mesoporous silica SBA-15 can enhance the solubility and dissolution rate of piperine.